Wireless Power Transfer Systems With Composite Cores for Magnetic Field Shielding With Electric Vehicles - Duan, Xianyi; Lan, Junqing; Kodera, Sachiko; Kirchner, Jens; Fischer, Georg; Hirata, Akimasa (IEEE Access, 2023)
The transmitting and receiving coils used in wireless power transfer (WPT) systems in electric vehicles (EVs) have a larger air gap (300 mm) and higher transmission power (kW) than those in typical WPT systems used in electrical appliances. However, this could weaken the magnetic field, reduce transfer efficiency, and lead to a public concern regarding potential adverse health effects related to electromagnetic field (EMF) exposure. Therefore, the assessment of compliance with product safety standards, based on international exposure guidelines such as the International Commission on Non-Ionizing Radiation Protection (ICNIRP), is crucial. This study uses the finite element method to analyze a commonly used core-less and core-based WPT system using a composite core material in EVs and scalar potential finite difference method for assessment of human protection. Based on the computational results, two core structures using different types of intermediate insert blocks were analyzed to reduce external magnetic fields and mitigate the human EMF exposure. The WPT system with a core structure improved the transfer efficiency by 34% for a 300 mm air gap over the core-less system. Moreover, this effectively reduced magnetic field leakage by 91.6% and induced electric field by 98.3%, resulting in the reduction of induced electric field in anatomical human body model. The results demonstrated that a WPT system with a composite core can simultaneously improve the transfer efficiency and protect humans from EMF exposure.
CRIS-Team Scopus Importer:2024-12-16
Keywords: electromagnetic interaction; EV WPT system; finite-element method; induced electric field; inductive coupling; wireless power transfer